Supplementary Figure S4 from Genomic Profiling of Metastatic Castration-Resistant Prostate Cancer Samples Resistant to Androgen Receptor Pathway Inhibitors - Naoual Menssouri (16617248) (2025)
Oncogenetic trees in patients with baseline tumors and resistant samples